ENTERPRISE RISK MANAGEMENT AND INTELLECTUAL CAPITAL DISCLOSURE : INVESTOR PERSPECTIVE - Yolanda, Yolanda; Ulum, Ihyaul; Setyawan, Setu (Universitas Muhammadiyah Malang)
This paper aims to examine the effect of corporate value on investor reactions with enterprise risk management (ERM) and intellectual capital disclosure (ICD) as a mediation variable on Indonesian companies listed in the Jakarta Islamic Index in 2016. The sample of this study consists of 25 companies with purposive sampling technique. Five ways numerical coding system and Partial Least Square (PLS) are used as a tool to perform data analysis. The results show that firm value has a significant influence on investor reaction. Unlike the ERM capable of mediating the relationship between corporate value and investor reactions, ICD is unable to mediate.